Feasibility and acceptability of the multi-component P3-MumBubVax antenatal intervention to promote maternal and childhood vaccination: A pilot study. Issue 24 (19th May 2020) - Kaufman, Jessica; Attwell, Katie; Tuckerman, Jane; O'Sullivan, Jacinta; Omer, Saad B.; Leask, Julie; Regan, Annette; Marshall, Helen; Lee, Katherine J.; Snelling, Tom; Perrett, Kirsten; Wiley, Kerrie; et al.
Highlights: P3-MumBubVax is a multi-component intervention to support maternal vaccine delivery by Australian midwives. The intervention targets all three levels of the healthcare encounter - the practice, provider and parent-levels (P3). It includes midwife prompts and vaccine communication training, website, fact sheets, and parent SMS reminders. Midwives and pregnant women reported that P3-MumBubVax was feasible and acceptable. Abstract: Background: Pregnancy is a critical time for vaccine decision-making, but coverage remains suboptimal for maternal influenza (45–60%) and pertussis vaccination (65–80%) in Australia. The multi-component P3-MumBubVax intervention has been designed for Australian midwives to optimise antenatal vaccine discussions and improve maternal and childhood vaccine uptake. A pilot study was conducted to assess intervention feasibility and acceptability. Methods: P3-MumBubVax includes components at three levels: 1. Practice ('vaccine champions'; stickers to prompt and record vaccine discussions/delivery); 2. Provider (website with vaccine communication training; learning exercise; fact sheets; links to child vaccination resources); 3. Parent (SMS reminders; website; fact sheets). Midwives and pregnant women 18–22 weeks gestation were recruited at the Royal Women's Hospital, Melbourne. Post-intervention online surveys assessed intervention feasibility, implementation, acceptability and impact on vaccine uptake. Results: Twenty-five midwives and 62 pregnant women were recruited and 19/25 midwives completed training. Surveys were returned by 18/25 midwives and 56/62 women. 14/18 midwives reported using the sticker prompts, 10/18 reported using or referring to the website, and 11/18 reported using the fact sheets. 48/56 pregnant women (86%) reported discussing influenza and 46/56 (82%) discussed pertussis vaccines with their midwives. These conversations were reported to be short (1–3 min) for 48/56 women (87%). All midwives were satisfied with the intervention and 17/18 reported feeling more confident discussing vaccines following the intervention. Women were very satisfied with SMS content (50/56; 94%) and timing (49/55; 89%), and with their vaccine discussions in general (34/56; 63%). However, 16/54 (30%) wanted more discussion about childhood vaccines. Self-reported maternal vaccine uptake was 82% (45/55) and 93% (51/55) for influenza and pertussis (baseline 2017–2018: 43% influenza, 60% pertussis) and 96% (50/52) of infants were fully vaccinated at 12 weeks. Discussion: The P3-MumBubVax intervention is feasible and acceptable in the Australian public antenatal setting. Further evaluation is required to determine effectiveness.